Mind wandering enhances statistical learning - Teodóra Vékony; Bence C. Farkas; Bianka Brezóczki; Matthias Mittner; Gábor Csifcsák; Péter Simor; Dezső Németh (iScience)
Summary: The human brain spends 30–50% of its waking hours engaged in mind-wandering (MW), a common phenomenon in which individuals either spontaneously or deliberately shift their attention away from external tasks to task-unrelated internal thoughts. Despite the significant amount of time dedicated to MW, its underlying reasons remain unexplained. Our pre-registered study investigates the potential adaptive aspects of MW, particularly its role in predictive processes measured by statistical learning. We simultaneously assessed visuomotor task performance as well as the capability to extract probabilistic information from the environment while assessing task focus (on-task vs. MW). We found that MW was associated with enhanced extraction of hidden, but predictable patterns. This finding suggests that MW may have functional relevance in human cognition by shaping behavior and predictive processes. Overall, our results highlight the importance of considering the adaptive aspects of MW, and its potential to enhance certain fundamental cognitive abilities.